Migrasi Iklim dan Keamanan Manusia: Tantangan Kebijakan untuk ASEAN dan Implikasi bagi Indonesia - Yulia Rimapradesi (Jurnal Hubungan Internasional Indonesia, 2025)
This study analyzes the interlinkages between climate change, human migration, and human security in Southeast Asia, focusing on ASEAN’s policy challenges and their implications for Indonesia. Using a qualitative approach through literature review, this research highlights climate-induced migration as a consequence of natural disasters, environmental degradation, and sea-level rise that threaten the dimensions of freedom from fear and freedom from want UNDPin 1994. Cases such as the Mekong Delta floods in Vietnam, typhoons in the Philippines, and forest fires in Indonesia demonstrate that climate migration has become a tangible human security issue. However, limited institutional capacity, economic disparities, and ASEAN’s non-interference principle hinder collective responses to this challenge. In Indonesia, climate adaptation policies have yet to fully integrate migration and human security considerations. This study recommends a reorientation of policy toward inclusive human security governance and the establishment of an ASEAN Framework on Climate Mobility to strengthen regional collaboration in addressing climate-induced migration in the future.